Prenatal low-dose Bisphenol A exposure impacts cortical development via cAMP-PKA-CREB pathway in offspring - Jiang, Chu; Guan, Jun; Tang, Xiangrong; Zhang, Yichun; Li, Xiangyu; Li, Yuting; Chen, Zhiheng; Zhang, Jing; Li, Jia-Da (Frontiers in Integrative Neuroscience, 2024)
Bisphenol A (BPA) is a widely used plasticizer known to cause various disorders. Despite a global reduction in the use of BPA-containing products, prenatal exposure to low-dose BPA, even those below established safety limits, has been linked to neurological and behavioral deficits in childhood. The precise mechanisms underlying these effects remain unclear. In the present study, we observed a significant increase in the number of cortical neurons in offspring born to dams exposed to low-dose BPA during pregnancy. We also found that this prenatal exposure to low-dose BPA led to increased proliferation but reduced migration of cortical neurons. Transcriptomic analysis via RNA sequencing revealed an aberrant activation of the cAMP-PKA-CREB pathway in offspring exposed to BPA. The use of H89, a selective PKA inhibitor, effectively rescued the deficits in both proliferation and migration of cortical neurons. Furthermore, offspring from dams exposed to low-dose BPA exhibited manic-like behaviors, including hyperactivity, anti-depressant-like responses, and reduced anxiety. While H89 normalized hyperactivity, it didn't affect the other behavioral changes. These results suggest that the overactivation of PKA plays a causative role in BPA-induced changes in neuronal development. Our data also indicate that manic-like behaviors induced by prenatal low-dose BPA exposure may be influenced by both altered neuronal development and abnormal PKA signaling in adulthood.